The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12030576
|View full text |Cite
|
Sign up to set email alerts
|

NUDT7 Loss Promotes KrasG12D CRC Development

Abstract: Studies have suggested that dysregulation of peroxisomal lipid metabolism might play an important role in colorectal cancer (CRC) development. Here, we found that KrasG12D-driven CRC tumors demonstrate dysfunctional peroxisomal β-oxidation and identified Nudt7 (peroxisomal coenzyme A diphosphatase NUDT7) as one of responsible peroxisomal genes. In KrasG12D-driven CRC tumors, the expression level of Nudt7 was significantly decreased. Treatment of azoxymethane/dextran sulfate sodium (AOM/DSS) into Nudt7 knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…NUDT7 and NUDT11 are both hydrolases that belong to the peroxisomal nudix family of enzymes ( 40 , 41 ). Mutations of NUDT7 have been described in colorectal cancer, inhibition of Nudt7 may contribute to the progression of Kras G12D colorectal cancer through upregulation of Wnt/β-catenin signaling and palmitic acid accumulation ( 42 ). Genetic and functional analyses showed that when NUDT11 was inhibited, colony formation of tumor-associated cell phenotypes was significantly reduced and their proliferation/survival capacity was compromised ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…NUDT7 and NUDT11 are both hydrolases that belong to the peroxisomal nudix family of enzymes ( 40 , 41 ). Mutations of NUDT7 have been described in colorectal cancer, inhibition of Nudt7 may contribute to the progression of Kras G12D colorectal cancer through upregulation of Wnt/β-catenin signaling and palmitic acid accumulation ( 42 ). Genetic and functional analyses showed that when NUDT11 was inhibited, colony formation of tumor-associated cell phenotypes was significantly reduced and their proliferation/survival capacity was compromised ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 the gene expression analysis of 30 cancer cell lines identified NUDT4 as a potential target [ 61 ]. The combination and analysis of muti-omic data revealed NUDT7 as having a role in colorectal and breast cancer development [ 62 , 63 ].…”
Section: Exploiting Global Signaling and Omic Data To Discover Novmentioning
confidence: 99%
“…Indeed, NUDT7 has been identified as a candidate susceptibility gene for familial CRC, with an early truncation, p.Y37X, found in two patients ( 109 ). Additionally, Nudt7 -/- mice treated with a combination of azoxymethane and dextran sulfate sodium develop more polyps and adenocarcinoma than WT mice ( 51 ). The changes in bile acid composition that stimulate the development of CRC have recently been linked to their effect on FXR activity ( 107 ), and deletion of Nudt7 affected FXR activity in a diet- and gender-specific manner ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nudt7 -/- mice have been recently generated ( 50 , 51 ). These mice exhibit compromised cartilage integrity and the propensity to develop more colonic polyps, but the effect of Nudt7 deletion on (acyl-)CoA levels and global hepatic metabolism has yet to be characterized.…”
mentioning
confidence: 99%